Did right-to-work laws impact income inequality? Evidence from U.S. states using the Synthetic Control Method - Aparna Mathur; Jeffrey L. Jordan; Abdul Munasib; Devesh Roy (American Enterprise Institute (AEI), 2016)
There is an ongoing debate about the effect of changes in labor regulations such as Right-to-Work (RTW) laws on rising income inequality in the U.S. In this paper, we use a relatively new methodology, the Synthetic Control Method – which we argue is more suitable for analyzing this data – to examine the impact of a state's adoption of an RTW law on income inequality. We use a wide range of inequality measures for states that enacted their RTW laws between the 1960s and the 2000s. Unlike some earlier papers that suggest a negative link between the RTW laws and correlates of inequality such as wages, we find that RTW laws had no significant impact on income inequality in these states.
Keywords: A; 330; Income inequality; collective bargaining